Recent Advances in Swarm Intelligence Algorithms and Their Applications - Dong, Jian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint comprises a collection of 20 articles that were accepted and published in the Special Issue titled " Recent Advances in Swarm Intelligence Algorithms and Their Applications" of the MDPI journal Mathematics. These articles cover a wide range of topics related to swarm intelligence algorithms and their theories. The topics include improvements in algorithm mechanisms, fusion algorithms, multiobjective optimization, and the optimization of large-scale problems, as well as the application of swarm intelligence in various fields such as engineering optimization problems, vehicle swarm motion, viscoelastic Maxwell-type DVA, and deep learning. It is hoped that this reprint will be helpful for scholars engaged in the field of swarm intelligence and also suitable for researchers interested in staying updated with the latest advancements in swarm intelligence algorithms and their applications. Nowadays, swarm intelligence is closely intertwined with various aspects of life. This reprint aims to provide readers with an understanding of these developments and further expand the application boundaries of such algorithms.